Concurrent Programming in C Made Easy - Dave, Parag H; Dave, H B (IETE journal of education, 2004)
Technology limitations forces us to investigate other methods of achieving high performance computer systems. Parallel computing is one such approach. Parallel programming is a relatively new and recent addition to traditional programming languages like C. While constructs have been suggested in literature to support Parallel programming, their implementation details have been left vague and undocumented. Also, in order to use the traditional programming constructs to implement the suggested Parallel programming constructs required costly time and effort on part of the programmer, especially in debugging since the effect of programs based on parallel programming are difficult to reproduce. This paper investigates selection of method of expression of concurrent operation, and design and implementation of a preprocessor so that such an effort is minimized, while maintaining the syntax and keywords used by pioneering investigators. These constructs are especially useful for teachers and students who wish to teach/study Operating System concepts.